Comportamiento de soluciones nutritivas en forraje verde hidropónico, usando semillas de sorgo sorghum vulgare en invernadero - León Macas, Luis Miguel (2009)
The investigation was carried out in the experimental farm Santa Inés of the Ability of Agricultural Sciences of the Technical University of Machala, located in the parish El Cambio. The used area was of 4,20 m of long for 1,20 of wide and a height of 2,90 m; divided in three wooden floors, the wooden trays (1,0 x 0,5 m); the watering system one carries out for nebulización. The objectives of the investigation were: 1. to determine the behavior from the sorghum to the different solution levels; 2. to evaluate the nutritional content of each treatment; 3. to establish the economic yield of the biomass taken place by the forage green hidropónico. Three more treatments were studied a witness, using a totally random design, the formulation of the FAO was used; for the treatment one you uses 1,25 solution cc TO and 0,5 solution cc B in each liter of water; for the treatment two you uses 2,5 solution cc TO and 1 solution cc B in each liter of water;; for the treatment three you uses 5 solution cc TO and 2 solution cc B in each liter of water; and the treatment four that is the witness one only carries out with water. In the first variable, statistically it was determined that the height of plants to the 5, 10 and 15 days, the highest average corresponded to T2 and the lowest to the T4. For the second variable the yield was determined statistically in weight, the average but high it was T2 and the lowest T4. In the analyses proximales taking like base the content of proteins turns out to be better the T2. The relationship, seed / forage was of 1:3,7. The first crops usually are not profitable, but the obtaining of numerous crops during the useful life of the infrastructure is profitable as it demonstrates it the economic analysis.